Genes in skin wound healing: microRNAs 2 - Sen, Chandan K. (Henry Stewart Talks, 2014)
miR-200b: potent angiostatic miRNA, Diabetic wounds, Wound closure and angiogenesis in diabetic wounds, miR-200b expression in diabetic wounds, GATA2 & VEGFR2, Biofilms: microbial social network, Multi-species biofilm infection in a swine burn wound model, Biofilm specific genes expressed in bacteria, Biofilm impairs tight junction function, Silencing of ZO-1 and ZO-2 by biofilms, Biofilm induces specific skin miRNA:miR-146a & miR-106b